Enhancing allergy diagnosis: mass spectrometry as a complementary technique to the basophil activation test - Wheeler, Nicole; Sanda, Miloslav; Rasool, Lanya; Elemary, Noha; Alpan, Arda; Safi, Hamed; Loizou, Denise; Plassmeyer, Matthew; Paige, Mikell; Ulrik Sonder, Soren; Alpan, Oral; Girgis, Michael (Frontiers in Allergy, 2025)
Accurate diagnostic tools for allergic conditions are essential for effective treatment. Traditional methods, such as skin prick tests (SPT) and specific IgE measurements are widely used, but they have limitations in sensitivity and specificity for certain allergens. While the Basophil Activation Test (BAT) offers improved specificity, particularly for allergens such as peanuts and sesame, its practicality and accessibility remain challenges. Mass spectrometry (MS) has recently gained recognition as a promising complementary tool in allergy diagnostics, offering high analytical precision and the capability to detect a wide range of allergen-specific biomarkers. This review explores the integration of MS into allergy diagnostics, emphasizing its potential to enhance BAT applications, particularly for non-responders. We discuss the underlying mechanisms, recent research highlighting its efficacy, and the technical challenges that must be addressed for clinical adoption. Additionally, we examine the standardization requirements and ethical considerations necessary for MS to become a routine diagnostic tool. Finally, we consider the future of allergy diagnostics, highlighting how MS technology could contribute to more precise, personalized, and patient-centered care in allergy management.